Most important bioethical dilemmas of people with long term disabilities - Rueda Castro, Laura; Miranda Zúñiga, Orquídea (Acta Bioethica, 2002)
The difficulty to achieve full participation and social integration of people with handicap is recognized at world level, situation that involves fundamental ethical values. The application of bioethic principles directed towards the professional chore under a new paradigm will signify an important contribution. Bioethic dilemmas, such as informed consent and the person's participation in making decisions that affect his own life, imply a challenge, the delivery of appropiate and opportune information, the development of professional behaviors that will favor the autonomy and recognition of these people as valid speakers. As to the subject of sexuality, professionals should allow everybody's integral development, recognizing sexuality as the human being's fundamental aspect, and faced to which you/they are entitled to be guided and educated taking into account their biographical history and what each one expects of his life (self determination). Therefore, they should be considered fundamental bioethic principles, such as Justice and Autonomy.